2013
DOI: 10.1350/clwr.2013.42.4.0259
|View full text |Cite
|
Sign up to set email alerts
|

Using International Law in Hong Kong Courts: An Examination of Non-Refoulement Litigation

Abstract: Hong Kong provides an interesting case study on the increasingly dynamic interaction between international law and domestic public law regimes. In a trilogy of cases, the Hong Kong courts have examined the domestic application of the international law of non-refoulement. These decisions addressed the potential influence of international law on constitutional rights, statutory interpretation, principles of judicial review, as well as the scope of the common law doctrine of incorporation. Having regard to common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…While Hong Kong is not party to the 1951 Refugee Convention, it is bound by seven core international human rights instruments which provide “explicit and implicit guarantees of non- refoulement ” or return (Loper, 2010: 405). This is closest to a legal obligation on the part of the HKSARG that is required to screen claimants and prevent the refoulement of individuals to a place where there are substantial grounds for believing that they would be subjected to torture, cruel, inhumane or degrading treatments (Ramsden and Marsh, 2013). Yet, the granting of the right not to be refouled is the only right asylum seekers or torture claimants possess in Hong Kong where they stay with limited security of residency.…”
Section: The Hong Kong Refugee Context and Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…While Hong Kong is not party to the 1951 Refugee Convention, it is bound by seven core international human rights instruments which provide “explicit and implicit guarantees of non- refoulement ” or return (Loper, 2010: 405). This is closest to a legal obligation on the part of the HKSARG that is required to screen claimants and prevent the refoulement of individuals to a place where there are substantial grounds for believing that they would be subjected to torture, cruel, inhumane or degrading treatments (Ramsden and Marsh, 2013). Yet, the granting of the right not to be refouled is the only right asylum seekers or torture claimants possess in Hong Kong where they stay with limited security of residency.…”
Section: The Hong Kong Refugee Context and Theoretical Frameworkmentioning
confidence: 99%
“…Although it is sometimes suggested that international conventions provide only very limited protection to “security of residence and work and welfare rights to asylum seekers” (Morris, 2007: 46). Increasingly, however, international human rights instruments are used in courts to challenge unfair policy practices in states (Morris, 2012; Ramsden and Marsh, 2013). Based on the Convention Against Torture and Other Cruel, Inhuman or Degrading Treatment or Punishment (CAT), an asylum seeker can make a ‘torture claim;’ similarly, he or she can also draw a cruel, inhuman or degrading treatment or punishment (CIDTP) claim under the International Covenant on Civil and Political Rights (ICCPR).…”
Section: The Hong Kong Refugee Context and Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation